Omega‐3 fatty acid add‐on nutritional immunotherapy delays progression to dementia in MCI patients on cholinesterase therapy: Human/Human trials: Nutraceuticals and non‐pharmacological interventions. (7th December 2020) - Fiala, Milan
Abstract: Background: Cholinesterase inhibitor (CI) drugs have cognitive benefits for one year but are not disease modifying. Omega‐3 fatty acids (omega‐3) with anti‐oxidants and resveratrol increase transcription of energy molecules, enhance phagocytosis of amyloid‐β (Aβ), increase monocyte/macrophages (MM) clearance of Aβ in the AD brain, and may be disease modifying. Method: We test cognition by MMSE, energy in peripheral blood mononuclear cells (PBMC) and macrophages using a) single cell RNA‐seq, b) respirometry in the Seahorse Analyzer; c) phagocytosis of fluorescent Aβ and P‐tau. We study glycans in PBMC using nanoLC/ESI‐QTOF‐MS system. Result: We enrolled into the study patients with cognitive problems who had been failing CI therapy according to neurologists and caregivers. We diagnosed study patients by neurological testing and imaging: 8 as subjective cognitive impairment (SCI), 7 as MCI, 1 as fronto‐temporal dementia (FTD), 2 as vascular cognitive impairment (VCI), and 3 as dementia with Lewy bodies (DLB). In the study, the patients added supplementation by omega‐3 fatty acid drink with anti‐oxidants and resveratrol (Smartfish) to CI. On these therapies, MCI patients maintained MCI status for >1 to 4.5 years and all improved Aβ immunity and activities of daily living in short term. The ω‐3 –supplemented MCI patients up regulated in vivo and in vitro glycolytic and TCA cycle enzymes and NAD synthesis enzyme NAMPT and increased Aβ phagocytosis. DLB and FTD patients progressed to dementia in 1 to 2 years, despite omega‐3. Conclusion: MCI patients have energy deficiency in macrophages and other immune cells. Omega‐3 provide ox‐phos energy for immune clearance of Aβ and neuronal homeostasis around the clock, thereby delaying progression to dementia.